(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Sugar and sugar derivatives have numerous reported biological activities. Sugar moieties in many therapeutically important compounds have influence on their pharmacological activities. Structure activity relationship studies have revealed the importance of sugar moieties in the structure of many clinically used drugs. This review focuses on the major biological activities such as anti-cancer, anti-diabetic, analgesic, anti-inflammatory, antiviral and antimicrobial activities of sugars and their derivatives including modified or synthetic sugar derivatives. The available reported structure activity relationship studies have also been described in this review. Biological investigation of different activities of sugar derivatives proves their suitability as one of the interesting classes of molecules for development of new drugs. Dhaka Univ. J. Pharm. Sci. 20(3): 381-394, 2022 (June) Centennial Special Issue